Numerical Modeling of a Gradiometric Coil Arrangement for Metal Sensing - Pólik, Z.; Kántor, Z. (Acta Technica Jaurinensis, 2012)
Transient response of metallic targets has been examined by numerical simulation in a gradiometric coil arrangement using a lowpass filtered current step excitation. The electrical conductivity and the magnetic permeability of the target materials were varied independently to unveil the specific contributions of these two material parameters. It was found that the amplitude, the zero crossing points and the overshoot of the gradiometric voltage signal are characteristic to the respective target material. For high conductivity targets, the magnetic property has a less pronounced influence to the shape and measures of the transient response signal, while a magnetic property plays a key role in the determination of the transient response for low conductivity targets.